Burnout syndrome in physical therapists - Demographic and organizational factors - Urszula Pustułka-Piwnik; Zdzisław Jan Ryn; Łukasz Krzywoszański; Joanna Stożek (Nofer Institute of Occupational Medicine, 2014)
Background: Professional burnout results from prolonged exposure to chronic, job-related stressors. According to Christina Maslach, professional burnout is a syndrome of emotional exhaustion, depersonalization and reduced personal accomplishment. Literature includes a number of reports on burnout syndrome within health service, but hardly ever do they make any references to physiotherapists. The purpose of this study is assessment of the level of professional burnout in a group of physiotherapists and investigating relationships between the indices of burnout syndrome and selected demographic as well as organizational variables. Material and Methods: The study group consisted of 151 physiotherapists with at least 3 years of experience, employed in various health service outposts in Krakow, Poland. The Maslach Burnout Inventory (MBI) was used to measure emotional exhaustion, depersonalization and personal accomplishment. A questionnaire for the description of socio-demographic and work characteristics was used as well. Results: Job burnout among the physiotherapists was manifested by an increased emotional exhaustion and decreased sense of personal achievement. Emotional exhaustion was significantly higher among physical therapists working with adults and employed in hospitals, depersonalization was higher among men, hospital workers and employees with seniority from 15 to 19 years, personal accomplishment was decreased among men and less-educated therapists. Conclusions: The study confirmed that indicators of burnout in physiotherapists are significantly associated with selected demographic and organizational variables. It is necessary to undertake a more exhaustive study of burnout in this group of employees, and implement elements of prevention. Med Pr 2014;65(4):453-462